2018
DOI: 10.1016/j.jalz.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric amyloid β preferentially targets neuronal and not glial mitochondrial‐encoded mRNAs

Abstract: Similarity of expression changes in neurons from Alzheimer's disease brain and neuronal cells treated with OAβ, and the effect of a CoQ analogue on the latter, suggests a pretreatment option to prevent OAβ toxicity, long before the damage is apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…However, studies about CoQ effect on neuronal mitochondria are scarce, although a decreased MRC activity and low ATP production due to neuronal CoQ deficiency has been observed [115]. Very recently, a novel CoQ analogue has been demonstrated to protect neuronal mitochondria from mitochondrial dysfunction caused by accumulation of oligomeric amyloid β (OAβ) in a neuronal model of AD [117]. This is in accordance with what we have observed in our work.…”
Section: Discussionsupporting
confidence: 91%
“…However, studies about CoQ effect on neuronal mitochondria are scarce, although a decreased MRC activity and low ATP production due to neuronal CoQ deficiency has been observed [115]. Very recently, a novel CoQ analogue has been demonstrated to protect neuronal mitochondria from mitochondrial dysfunction caused by accumulation of oligomeric amyloid β (OAβ) in a neuronal model of AD [117]. This is in accordance with what we have observed in our work.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been recently reported that amyloidβ specifically causes mitochondrial damage to neurones [49] and not to microglia or astrocytes [50]. Mitochondria are very mobile in axons and thus ongoing Ca 2+ influx or further phosphorylation of Tau, causing increasing mitochondrial damage, would not be limited to site of damage but would spread throughout the axon as more mitochondria were damaged over time (Fig.…”
Section: Lose the Synapse To Save The Axonmentioning
confidence: 86%
“…SH‐SY5Y cells (purchased from the Shanghai Institutes for Biological Sciences, China) were supplied with complete in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 2 m m glutamine. [ 55 ] To establish the in vitro model of tauopathy which was hyperphosphorylation of tau, SH‐SY5Y cells were induced by incubation with okadaic acid (OA, Sigma) at a final concentration of 20 n m for 24 h as a previous work, [ 19 ] and neurons were induced by incubation with OA at a final concentration of 10 n m for 4 h, according to the different sensitivity to OA. For cell treatment, OA‐damaged SH‐SY5Y cells or neurons were replaced with CM or HGF, while Con and OA‐damaged groups were replaced with α ‐MEM.…”
Section: Methodsmentioning
confidence: 99%